2018
DOI: 10.1021/acssuschemeng.7b03158
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pH Responsive Hydrogels Using Methacrylated Lignosulfonate Cross-Linker: Synthesis, Characterization, and Properties

Abstract: In this work, biobased hydrogels with temperature and pH responsive properties were prepared by copolymerizing N-isopropyl­acrylamide (NIPAM), itaconic acid (IA), and methacrylated lignosulfonate (MLS), where the multifunctional MLS served as a novel macro-cross-linker. The network structures of the lignosulfonate-NIPAM-IA hydrogels (LNIH) were characterized and confirmed by elemental analysis, Fourier transform infrared, and 13C nuclear magnetic resonance. The equilibrium swelling capacity of the LNIH hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 36 publications
(58 reference statements)
1
43
0
Order By: Relevance
“…Figure 3 shows the interior morphological structures of freeze-dried GNCH with different GPTMS contents. All the hydrogels display a continuous and porous three-dimensional structure, which is caused by phase separation and sublimation of removing water during the freeze-drying process [41]. In addition, the pore size of hydrogel became larger as GPTMS contents increased.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the interior morphological structures of freeze-dried GNCH with different GPTMS contents. All the hydrogels display a continuous and porous three-dimensional structure, which is caused by phase separation and sublimation of removing water during the freeze-drying process [41]. In addition, the pore size of hydrogel became larger as GPTMS contents increased.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the gel pore sizes in Figure 8a–d, it was found that the pore size of the first gel was slightly smaller than the second one. This is because the observed porous structure of freeze-dried hydrogels were due to the phase separation of the gels during rapid freezing and subsequent removal of the water by sublimation which left voids in place where the water previously occupied, and the increased cross-link density results in the second gel faster phase separation during freezing [43]. Then, comparing the changes of the two gels between 25 °C with 40 °C, it can be seen that the gel was in a shrinking state at 40 °C, and the pore size of three-dimensional network become smaller.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the content of lignin in hydrogels significantly improved the mechanical properties of the hydrogels [439] and they show excellent strength properties. The biodegradation of the lignin-based hydrogel depends on the crosslink density and the phenolics content in the hydrogel.…”
Section: Hybrid Hydrogels Containing Lignin For Biomedical Applicationsmentioning
confidence: 98%